Analisis Pengetahuan dan Kepatuhan Perawat dalam Penerapan Pencegahan Resiko Pasien Jatuh di Ruang Rawat Inap Rumah Sakit PKU Muhammadiyah Kartasura - Laily Nur Azizah; Asti Nurhayati (Jurnal Sains dan Kesehatan, 2024)
Patient safety includes safe care, risk assessment, risk management, and incident reporting. The most frequent patient safety incidents are falls, which rank second after medication errors. Objective: To analyze the knowledge and compliance of nurses in implementing prevention for patients at risk of falls in the inpatient room at PKU Muhammadiyah Kartasura Hospital. Method: This research uses mixed methods, which combines collection, analysis and mixing of quantitative and qualitative data in one study. The research population was 20 nurses at the PKU Muhammadiyah Kartasura Hospital Inpatient Installation in 2024. Results: Respondents aged 26-35 years (45%), female (85%), last education was D-III Nursing (80%), and length of service 1-5 years (40%). Most respondents had a high level of knowledge (70%), and high compliance (80%). Nurses with poor knowledge who did not comply were 66.7%, while all nurses with good knowledge complied 100%. Chi-square analysis was 0.003, showing that compliance was influenced by level of knowledge, length of work, age, and self-awareness. Conclusion: A nurse's compliance cannot be separated from the nurse's level of knowledge in implementing risk prevention for patient falls. Apart from the level of knowledge, length of work and a person's age also greatly influence the implementation of risk prevention for patient falls, a person's lack of self-awareness can also influence a person's compliance to progress and be successful.